A Sustainable Process for the Production of Varnishes Based on Pelargonic Acid Esters. (11th February 2019) - Benessere, Vincenzo; Cucciolito, Maria E.; De Santis, Augusta; Di Serio, Martino; Esposito, Roberto; Melchiorre, Massimo; Nugnes, Fiorella; Paduano, Luigi; Ruffo, Francesco
Abstract: This work demonstrates the possibility of using pelargonic acid (PA) esters as solvents for vegetable‐based varnishes. First, PA was efficiently produced through a chemocatalytic cleavage of oleic acid, practicing an optimized scale‐up of previously developed conditions. PA was then esterified with several alcohols ROH (R = Me, i ‐Pr, n ‐Bu, n ‐Hex, 2‐ethylhexyl, and sec ‐octyl) and the products were formulated with a commercial rosin (Phenolic Modified Rosin Esters). Dynamic light scattering (DLS) measures and determination of rheological parameters of the corresponding varnishes disclosed their suitability for applications in offset, coldset, heatset printing inks, and coatings. Furthermore, inks obtained were used to efficiently produce preliminary industrial offset prints.